Effects of Zamzam water on glycemic status, lipid profile, redox homeostasis, and body composition in rats. Issue 1 (February 2020) - AlJuwaie, Ghadeer F.; Latif, Rabia; AlSheikh, Mona H.; Al Sunni, Ahmed; Chathoth, Shahanas
الملخص : أهداف البحث: أظهرت الدراسات آثارا مفيدة لماء زمزم للعديد من الأمراض كالسكري، وتسمم الكلى، وتسمم الكبد، والضغط العصبي. تم تصميم الدراسة الحالية لتقييم تأثيرات ماء زمزم على حالة السكر في الدم، ومستوى الدهون، وتوازن مضادات الأكسدة، وتكوين الجسم في الفئران السليمة. طرق البحث: تم تقسيم ٢٤ فأرا إلى مجموعتين متساويتين. بحيث تم تغذية الفئران على حمية تشاو جنبا إلى جنب مع ماء الصنبور، أو ماء زمزم كمصدر للسوائل فقط. بعد ١٠ أسابيع، تم قياس مستوى السكر في الدم أثناء الصيام، والانسولين في الدم، ومقاومة الأنسولين، والبروتين الدهني منخفض الكثافة، والبروتين الدهني عالي الكثافة، وديسميوتاز سوبرأوكسيد، وبيروكسيد الدهون. كما تم وزن الكتلة الدهنية والجسدية (العضلات والعظام فقط) وحساب وزن الجسم المتبقي. النتائج: انخفضت النتائج التالية بشكل ملحوظ في مجموعة ماء زمزم مقارنة بمجموعة ماء الصنبور السكرفي الدم أثناء الصيام ٩٦.٥ مقابل ١٤٧.١ ملغم/دسل، والأنسولين في الدم ٠.٤٤ ضد ١.٣١ ومقاومة الانسولين ١.٨٩ ضد ٨.٤٠ ولم يكن هناك أي تغير ملحوظ في البروتين الدهني منخفض الكثافة، والبروتين الدهني عالي الكثافة، وديسميوتاز سوبرأوكسيد، وبيروكسيد الدهون، ووزن الجسم، والكتلة الدهنية، والجثة، ووزن الجسم المتبقي (المطلقة والنسبية على حد سواء). الاستنتاجات: أظهرت دراستنا أن استهلاك ماء زمزم لمدة ١٠ أسابيع يؤدي إلى انخفاض مستوى السكر في الدم أثناء الصيام، والأنسولين في الدم ومقاومة الانسولين. ولكن لا يوجد أي تأثير لماء زمزم على مستوى الدهون، وتوازن مضادات الأكسدة وتكوين الجسم. Abstract: Objectives: Previous studies have demonstrated that Zamzam water exerts beneficial effects on several ailments such as diabetes mellitus, nephrotoxicity, hepatotoxicity, and stress. The present study aimed to assess the effects of Zamzam water on glycemic status, lipid profile, redox homeostasis, and body composition in healthy rats. Methods: Twenty-four rats were divided into two equal groups. Rats were fed a chow diet along with either tap or Zamzam water as the only fluid source. After ten weeks, fasting blood glucose, serum insulin, insulin resistance, low density lipoproteins (LDL) cholesterol, high density lipoprotein (HDL) cholesterol, superoxide dismutase, and lipid peroxidation were measured. Adipose pads and carcass (musculoskeletal only) were weighed and residual body weight was calculated. The groups were compared using independent sample t test (unpaired). Results: The following parameters were significantly reduced in the Zamzam water group compared to the tap water group: fasting blood sugar, 96.5 vs. 147.1 mg/dl ( p  = 0.00); serum insulin, 0.44 vs. 1.31 μU/l ( p  = 0.00); and insulin resistance, 1.89 vs. 8.40 ( p  = 0.00). LDL cholesterol, HDL cholesterol, superoxide dismutase, lipid peroxidation, weight of the body, fat pads, and carcass, as well as residual body weight (both absolute and relative) showed no significant changes. Conclusion: Zamzam water intake for ten weeks decreases fasting blood sugar, serum insulin, and insulin resistance. However, Zamzam water has no effect on lipid profile, redox homeostasis, and body composition.